ANTIHYPERGLYCAEMIC AND ANTIOXIDANT EFFECTS OF ADENIA LOBATA ENGL. (PASSIFLORACEAE) IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Joseph, Sarkodie Adusei; Theophilus, Fleischer Christian; Dominica, Edoh Adotei; Rita, Dickson Akosua; Kwaw, Mensah Lincoln; Kofi, Annan; Eric, Woode; George, Koffour Asumeng; Alfreda, Appiah Ampomah; Henry, Brew-Daniels (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The antihyperglycaemic and antioxidant activities of a Ghanaian medicinal plant namely Adenia lobata Engl (Passifloraceae), used to treat diabetes mellitus in traditional medicine, was investigated. The dried stem powder of A. lobata was successively extracted by Soxhlet with petroleum ether and 70% ethanol to obtain the crude petroleum ether (PEAL: yield =1.1w/w %) and ethanol (EEAL: yield = 5.4 w/w %) extracts. The extracts were assessed for their antihyperglycaemic and antioxidant activities. The antihyperglycaemic activity of PEAL and EEAL were determined in streptozotocin-induced diabetic rats (70 mg/kg body weight). Five groups of diabetic rats were given 150, 300 and 600 mg/kg body weight of PEAL and EEAL orally once daily for 20 days. Glibenclamide (5 mg/kg body weight) was used as positive control while distilled water (5 ml) acted as the normal diabetic control. The blood glucose levels were monitored initially for 6 hours and subsequently over 24 days. Both extracts exhibited statistically significant (p< 0.001) antihyperglycaemic activity throughout the study period, with EEAL showing the greatest activity. The antioxidant properties of the petroleum ether and ethanol extracts of A. lobata (PEAL and EEAL) were evaluated using five assays; total phenolic content, total antioxidant capacity, reducing power, DPPH scavenging effect and lipid peroxidation activity. In all these assays, the antioxidant properties increased with increasing concentration of the extracts.